Ireland's Discovery Programme : progress and prospect - Waddell, John
Much archaeology is publicly funded, but rarely as a venture that is the personal initiative of a head of government. In this invited contribution, John Waddell (National University of Ireland, Galway) reports on the vigorous initiative of the Irish Discovery Programme since its 1991 launch. (And ANTIQUITY's editor notes the speedy rhythm of publication, in which John Waddell has had a role!)